ENLARGEMENT OF THE EUROPEAN UNION IN THE CONTEXT OF UKRAINE, MOLDOVA, AND GEORGIA’S MEMBERSHIP APPLICATIONS - Maria-Cristina SOLACOLU (Challenges of the Knowledge Society)
Ever since the foundation of the European Communities during the 1950s, enlargement of these organisations has been an important goal, as well as, in some cases, a challenge to the existing legal and political paradigm. In this article we set out to present the evolution of the accession process and the particularities present in specific cases, specifically those of the countries forming what is called the Eastern Neighbourhood, in order to evaluate Ukraine, Moldova, and Georgia’s likelihood of becoming a fully-fledged member of the European Union, and the probable timeline.